Mitigation of antibiotic resistance risk in aerobic sludge by zero-valent iron: From pathogen reduction to conjugation inhibition and network weakening - Ying Wu; Lin Zhu; Guoping Lin; Xuezhu Han; Jingpeng Li; Jiaming Yi; Dan Huang; Meizhen Wang (Bioresource Technology, 2026)

Multiscale solvation-electronic regulation strategy toward stable Zn anode - Jiaqi Li; Yushan Ma; Yicheng Wang; Shaoyu Zhang; Jiaming Li; Nan Li; Junyi Han; Hedong Gu; Zhanhong Yang; Xiaolei Wang (Chemical Engineering Journal, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Freeze–thaw cycles control successive glacier landslide hazards in Amney Machen Mountain - Jiaming Ye; Ruochen Jiang; Shihao Xiao; Yingyue Han; Luyu Ju; Wenjun Lu; Ruiqiang Bai; Tao Yao; Limin Zhang (Landslides, 2026)
Climate change has markedly increased the susceptibility of glacier-related landslides to alpine environments, leading to cascading processes with catastrophic impacts. Nevertheless, their triggering processes remain inadequately understood, which hinder robust hazard assessments and effective risk mitigation. Glacier collapses and cascading processes have been frequently observed at Xiaoma Gully in Amney Machen Mountain. Based on remote sensing, meteorological data analyses, field surveys and numerical simulations, glacier landslide hazard chains in this gully are reconstructed and associated triggers are identified. Results indicate that extreme diurnal freeze–thaw cycles drove the Xiaoma glacier collapses, and extreme temperature and precipitation accelerated glacier instabilities. The 365-day cumulative number of diurnal freeze–thaw cycles is identified as a critical precursor for initiating glacier collapses, serving as a quantitative indicator to characterize the long-term impact of freeze–thaw cycles. The application of this indicator to the Kolka Glacier collapse at Genaldon Valley in Russian Caucasus further demonstrates its feasibility. Furthermore, the catastrophic glacier landslide cascades underwent hazard-type transformation and displayed high mobility, reaching peak flow velocities over 30 m/s. This study sheds light on early warning and emergency management of glacier collapses in alpine regions.

Fully coupled numerical model of moored structures-mooring line-ice ridge interaction - Jiaming Chen; Shengjie Rui; Sen Han; Shifeng Ding; Jie Tan; Li Zhou (Ocean Engineering, 2026)

A novel multifunctional bacterial consortium synergistically promotes rhizoremediation of dibutyl phthalate and cucumber growth: Insights from multi-omics analyses - Jiaming Xu; Yan Li; Haoyan Han; Yi Wu; Yue Tao; Yuexuan Ma; Zhao Jiang; Ying Zhang (Journal of Environmental Sciences, 2026)

Mass and Energy Balance-Oriented Allocation Mechanism for Petrochemical Product Carbon Footprint - Lili Sun; Hongju Chen; Hetian Zhu; Xiaotong Li; Jiaming Gu; Yinghui Han; Guofei Shen; Yunhu Gao; Baojuan Dou; Chong Wei; Qun Shen; Wei Wei (Aerosol Science and Engineering, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Genome-wide identification of oat EIL gene family and analysis of expression patterns under abiotic stress - Xiaodong Guo; Xuanyu Liu; Jiaming Nie; Qidi Zhang; Simeng Cai; Huiyan Liu; Bing Han; Hongbin Zhao (Genetic Resources and Crop Evolution, 2026)

Effect of aquatic animal combination and their density on the removal of Microcystis aeruginosa from wastewater - Jiaming Zheng; Shanshan Xie; Xiangyong Zheng; Wenjuan Han; Min Zhao (Aquatic Ecology, 2026)

Synergistic effect in dual-site catalyst with silanol-stabilized Co2+-bonded Ni clusters for methane dry reforming - Zijun Huang; Dedong He; Han Xiao; Jun Liang; Jiaming Dong; Zhenzhong Tao; Xiaohua Cao; Dingkai Chen; Yongming Luo (Chemical Engineering Journal, 2026)

Metformin drives the antibiotic resistome in activated sludge by reshaping microbial communities and promoting horizontal gene transfer - Jiaming Yi; Zhengtao Li; Xuezhu Han; Jingpeng Li; Haotian Liu; Lin Zhu; Meizhen Wang (Journal of Hazardous Materials, 2026)

The effect of hydroxyl groups and humidity on the adsorption capacity of amine-functionalized macroporous resins for direct air capture - Jiaming Wang; Xiaohan Weng; Tao Han; Yongqiang Wang; Jinning Yang; Chao Zhou; Dong Xu; Liying Liu (Chemical Engineering Journal, 2025)

Gastrodin inhibits hexokinase-2 mediated glycolysis to rescue rotenone-damaged PC12 cells - Min Chen; Jiaming Tian; Buyun Jia; Meng Wang; Anqi Han; Jiming Zhu; Shasha Tian; Xiaoming Gao; Baikun Li; Qinglin Li; Shanshan Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A performance improving method of preparing nonlinear conductive coating for HVDC insulator based on plasma treatment technology: For lower-additive amounts and higher adhesive stability - Zijun Pan; Jiaming Cheng; Quanyou Nie; Zirui Wu; Yujie Qiu; Yuhan Ye; Shiyi Mao; Pu Han; Cheng Pan; Ju Tang (Chemical Engineering Journal, 2025)

Adipose-derived soluble fractions activated bioink promotes cutaneous repair and regeneration via mobilizing endogenous reparative cells - Wei Zhang; Jiaming Shao; Hanlei Zhou; Min Yang; Chenghao Cai; Fang He; Yiran Wang; Pengqin Xu; Sizhan Xia; Tingting Weng; Jialiang Wang; Ronghua Jin; et al. (Chemical Engineering Journal, 2025)

Integrated multi-omics reveals mechanistic impact of gut microbiota inhibition on lignocellulose biodegradation in Tenebrio molitor - Xinrui Mao; Jiaming Li; Wenbiao Jin; Wei Han (Bioresource Technology, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

Differential impacts of rain event and continuous rainfall on biological phosphorus removal of a full-scale wastewater treatment plant: performance analysis and optimization strategies - Jiaming Hu; Lu-Man Jiang; Lihua Wang; Xinya Ding; Xinhong Han; Yan Zhang; Haijuan Wei; Zhan Qiu; Ying An; Zhen Zhou (Journal of Environmental Management, 2025)

Large-area crack-free photonic crystals coating on leather with brilliant and robust iridescent structural color - Jingyuan Hu; Yaqun Han; Xin Sun; Wenbo Wu; Jiaming Huyan; Suli Wu (Chemical Engineering Journal, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Characterization and risk-quantification of antibiotic resistome in grain-based and non-grain cropping soils - Jingpeng Li; Lin Zhu; Xiaodi Li; Xuezhu Han; Jiaming Yi; Ying Wu; Meizhen Wang (Environmental Pollution, 2025)

Near-white light-emitting copper nanoclusters/starch composites for multiplexing imaging and multichannel enhancement of latent fingerprints - Zhibo Gao; Chuanjun Yuan; Ming Li; Zhize Xu; Meng Wang; Jiaming Lyu; Shiqiang Sun; Fenghe Liu; Peiliang Han (Chemical Engineering Journal, 2025)

Mechanism of rice bran removal at individual grain and population levels in abrasive rice mill - Ze Sun; Xinlei Wang; Anqi Li; Jiaming Fei; Wenyu Feng; Dan Zhao; Yanlong Han; Fuguo Jia; Hao Li; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2025)

Interface catalysis over AlPO4/Al2O3 with F-Al-O species for resource utilization of hydrofluorocarbon greenhouse gas - Yiwei Sun; Xiaoli Wei; Fangcao Liu; Bing Liu; Jiaming Zhao; Yubao Bi; Wenfeng Han (Journal of Environmental Chemical Engineering, 2025)

Selective complex leaching of Cu, Zn, and Cd from recycled copper smelting fly ash using NH3-NH4Cl system and kinetic analysis - Fan Lin; Tianya Lei; Jiancheng Shu; Mengjun Chen; Jibamu Duo; Xiangfei Zeng; Yunhui Han; Shaoqin Chen; Jiaming Chen; Weiping Huang; Jun Luo (Process Safety and Environmental Protection, 2025)

Enhanced removal of Cr(VI) from aqueous solutions by an electric field and iron–manganese oxalate composites - Shushu Liao; Kaiyuan Liang; Jiancheng Shu; Yunhui Han; Jiaming Chen; Shaoqin Chen; Jun Luo; Shengjie Wang; Mengjun Chen; Hanke Wei; Zongyu Deng (Journal of Environmental Chemical Engineering, 2025)

Integrating UAV, UGV and UAV-UGV collaboration in future industrialized agriculture: Analysis, opportunities and challenges - Zhigang Ren; Han Zheng; Jian Chen; Tao Chen; Pengyang Xie; Yunzhe Xu; Jiaming Deng; Huanzhe Wang; Mingjiang Sun; Wenchi Jiao (Computers and Electronics in Agriculture, 2024)

Investigation of rice debranning mechanism based on tribological behaviour between rice grains - Jiaming Fei; Ze Sun; Dan Zhao; Anqi Li; Fuguo Jia; Yanlong Han; Hao Li; Shouyu Ji; Zhuozhuang Li; Wenyu Feng (Biosystems Engineering, 2024)

Influence of staggered guide vane on hydraulic performance of reactor coolant pump - Binhao Liu; Daoxing Ye; Junlin Chen; Mengke Wu; Rui Deng; Junyu Zhang; Jiaming Han (Annals of Nuclear Energy, 2024)

Enhanced photocatalytic CO2 reduction to CH4 on oxygen vacancy-rich NiCo2O4 with surface pits: Synthesis, DFT calculations, and mechanistic insights - Jiaming Li; Yuan Li; Minsu Han; Yusuke Yamauchi; Gaoke Zhang (Chemical Engineering Journal, 2024)

A study on ice resistance prediction based on deep learning data generation method - Qianyang Sun; Jiaming Chen; Li Zhou; Shifeng Ding; Sen Han (Ocean Engineering, 2024)

Effects of polymerization types on plastics ingestion and biodegradation by Zophobas atratus larvae, and successions of both gut bacterial and fungal microbiomes - Yue Weng; Xiaoyu Han; Huayang Sun; Jiaming Wang; Yumeng Wang; Xin Zhao (Environmental Research, 2024)

Responses of physiological, microbiome and lipid metabolism to lignocellulose wastes in gut of yellow mealworm (Tenebrio molitor) - Xinrui Mao; Jiaming Li; Enqing Meng; Wenbiao Jin; Wei Han (Bioresource Technology, 2024)

Establishment of a gill cell line from yellowfin seabream ( Acanthopagrus latus ) for studying Amyloodinium ocellatum infection of fish - Zhicheng Li; Jingyu Zhuang; Jiaming Chen; Jizhen Cao; Qing Han; Zhi Luo; Baotun Wang; Hebing Wang; Anxing Li (Journal of Fish Diseases, 2024)
Amyloodinium ocellatum is among the most devastating protozoan parasites, causing huge economic losses in the mariculture industry. However, the pathogenesis of amyloodiniosis remains unknown, hindering the development of targeted anti‐parasitic drugs. The A. ocellatum in vitro model is an indispensable tool for investigating the pathogenic mechanism of amyloodiniosis at the cellular and molecular levels. The present work developed a new cell line, ALG, from the gill of yellowfin seabream ( Acanthopagrus latus ). The cell line was routinely cultured at 28°C in Dulbecco's modified Eagle medium (DMEM) supplemented with 15% fetal bovine serum (FBS). ALG cells were adherent and exhibited an epithelioid morphology; the cells were stably passed over 30 generations and successfully cryopreserved. The cell line derived from A. latus was identified based on partial sequence amplification and sequencing of cytochrome B ( Cyt b ). The ALG was seeded onto transwell inserts and found to be a platform for in vitro infection of A. ocellatum , with a 37.23 ± 5.75% infection rate. Furthermore, scanning electron microscopy (SEM) revealed that A. ocellatum parasitizes cell monolayers via rhizoids. A. ocellatum infection increased the expression of apoptosis and inflammation‐related genes, including caspase 3 ( Casp 3 ), interleukin 1 ( IL‐1 ), interleukin 10 ( IL‐10 ), tumour necrosis factor‐alpha ( TNF‐α ), in vivo or in vitro. These results demonstrated that the in vitro gill cell monolayer successfully recapitulated in vivo A. latus host responses to A. ocellatum infection. The ALG cell line holds great promise as a valuable tool for investigating parasite–host interactions in vitro.

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

Reduced moisture caused by short-term grazing prohibition results in a significant decrease of fungi abundance - Hongbin Zhao; Xiaofu Zhang; Huiyan Liu; Xue Bai; Jiaming Nie; Guodong Han; Bing Han (Journal of Arid Environments, 2024)

Image-guided structure-constrained inversion of electrical resistivity data for improving contaminations characterization - Xinmin Ma; Jieyi Zhou; Jing Li; Jiaming Zhang; Chunmei Han; Lili Guo; Shupeng Li; Deqiang Mao (Computers & Geosciences, 2024)

Distribution patterns and influential factors of pathogenic bacteria in freshwater aquaculture sediments - Wenxiang Xi; Xun Zhang; Xianbin Zhu; Jiaming Wang; Han Xue; Hongzhong Pan (Environmental Science and Pollution Research, 2024)

Ingestion and biodegradation of disposable surgical masks by yellow mealworms Tenebrio molitor larvae: Differences in mask layers and effects on the larval gut microbiome - Jiaming Wang; Chi Zhang; Xin Zhao; Yue Weng; Xinrui Nan; Xiaoyu Han; Chen Li; Baoqin Liu (Science of The Total Environment, 2023)

Occurrence and fate of antibiotics and ARGs in a wastewater treatment plant with JHB process in Guangzhou, South China: Removal performance, interaction and host analysis - Yuepeng Deng; Huaihao Xu; Yuting Gu; Yongyin Lan; Junpeng Diao; Zhijian Xiao; Jiaming Zhu; Biqing Li; Jie Zou; Kaoming Zhang; Yuxian Liu; Jingchuan Xue; et al. (Journal of Water Process Engineering, 2023)

Non-uniform milling caused by preferential orientation of rice grains in friction rice mills - Jiaming Fei; Wenyu Feng; Shaohang Shen; Yanlong Han; Anqi Li; Xianzhi Hao; Fuguo Jia; Ze Sun; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2023)

Ingestion preference and efficiencies of different polymerization types foam plastics by Tenebrio molitor larvae, associated with changes of both core gut bacterial and fungal microbiomes - Yijing Wang; Xin Zhao; Jiaming Wang; Yue Weng; Yumeng Wang; Xin Li; Xiaoyu Han (Journal of Environmental Chemical Engineering, 2023)

Evolutionary characterization and pathogenicity of Getah virus from pigs in Guangdong Province of China - Jinghua Pan; Haoquan Zhang; Xiuqiao Chen; Mengyi Zeng; Hui Han; Yajing Guo; Jiaming Li; Shicheng Luo; Guangzhi Yan; Shengnan Chen; Meilian Mo; Mingjie Liu; et al. (Archives of Virology, 2023)

Numerical investigation of flow similarity of rice grains in friction rice mill and establishment of scale-up rule - Anqi Li; Fuguo Jia; Jiaming Fei; Yanlong Han; Peiyu Chen; Wenyu Feng; Xianzhi Hao; Shaohang Shen; Hao Li (Computers and Electronics in Agriculture, 2023)

The carbon reduction effects of stepped carbon emissions trading and carbon capture and storage on hybrid wind-PV-thermal- storage generation operating systems - Yongmei Wei; Xinyu Wang; Jin Zheng; Yihong Ding; Jiaming He; Jian Han (Environmental Science and Pollution Research, 2023)

Study on dynamic response mechanism of rice grains in friction rice mill and scale-up approach of parameter based on discrete element method - Anqi Li; Fuguo Jia; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Xianzhi Hao; Jiaming Fei; Shaohang Shen; Wenyu Feng (Innovative Food Science & Emerging Technologies, 2023)

From remotely‐sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part II—Harnessing data - Ying Sun; Jiaming Wen; Lianhong Gu; Joanna Joiner; Christine Y. Chang; Christiaan van der Tol; Albert Porcar‐Castell; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Although our observing capabilities of solar‐induced chlorophyll fluorescence (SIF) have been growing rapidly, the quality and consistency of SIF datasets are still in an active stage of research and development. As a result, there are considerable inconsistencies among diverse SIF datasets at all scales and the widespread applications of them have led to contradictory findings. The present review is the second of the two companion reviews, and data oriented. It aims to (1) synthesize the variety, scale, and uncertainty of existing SIF datasets, (2) synthesize the diverse applications in the sector of ecology, agriculture, hydrology, climate, and socioeconomics, and (3) clarify how such data inconsistency superimposed with the theoretical complexities laid out in (Sun et al., 2023) may impact process interpretation of various applications and contribute to inconsistent findings. We emphasize that accurate interpretation of the functional relationships between SIF and other ecological indicators is contingent upon complete understanding of SIF data quality and uncertainty. Biases and uncertainties in SIF observations can significantly confound interpretation of their relationships and how such relationships respond to environmental variations. Built upon our syntheses, we summarize existing gaps and uncertainties in current SIF observations. Further, we offer our perspectives on innovations needed to help improve informing ecosystem structure, function, and service under climate change, including enhancing in‐situ SIF observing capability especially in “data desert” regions, improving cross‐instrument data standardization and network coordination, and advancing applications by fully harnessing theory and data.

From remotely sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part I—Harnessing theory - Ying Sun; Lianhong Gu; Jiaming Wen; Christiaan van der Tol; Albert Porcar‐Castell; Joanna Joiner; Christine Y. Chang; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Solar‐induced chlorophyll fluorescence (SIF) is a remotely sensed optical signal emitted during the light reactions of photosynthesis. The past two decades have witnessed an explosion in availability of SIF data at increasingly higher spatial and temporal resolutions, sparking applications in diverse research sectors (e.g., ecology, agriculture, hydrology, climate, and socioeconomics). These applications must deal with complexities caused by tremendous variations in scale and the impacts of interacting and superimposing plant physiology and three‐dimensional vegetation structure on the emission and scattering of SIF. At present, these complexities have not been overcome. To advance future research, the two companion reviews aim to (1) develop an analytical framework for inferring terrestrial vegetation structures and function that are tied to SIF emission, (2) synthesize progress and identify challenges in SIF research via the lens of multi‐sector applications, and (3) map out actionable solutions to tackle these challenges and offer our vision for research priorities over the next 5–10 years based on the proposed analytical framework. This paper is the first of the two companion reviews, and theory oriented. It introduces a theoretically rigorous yet practically applicable analytical framework. Guided by this framework, we offer theoretical perspectives on three overarching questions: (1) The forward (mechanism) question —How are the dynamics of SIF affected by terrestrial ecosystem structure and function? (2) The inference question : What aspects of terrestrial ecosystem structure, function, and service can be reliably inferred from remotely sensed SIF and how? (3) The innovation question : What innovations are needed to realize the full potential of SIF remote sensing for real‐world applications under climate change? The analytical framework elucidates that process complexity must be appreciated in inferring ecosystem structure and function from the observed SIF; this framework can serve as a diagnosis and inference tool for versatile applications across diverse spatial and temporal scales.

The mechanism of bran layer removal in friction rice mills - Jiaming Fei; Wenyu Feng; Fuguo Jia; Yanlong Han; Peiyu Chen; Anqi Li; Yinglong Wang; Jincheng Zhang; Shaohang Shen; Xianzhi Hao (Biosystems Engineering, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Improving the detection accuracy of the nitrogen content of fresh tea leaves by combining FT-NIR with moisture removal method - Jiaming Guo; Han Huang; Xiaolong He; Jinwei Cai; Zhixiong Zeng; Chengying Ma; Enli Lü; Qunyu Shen; Yanhua Liu (Food Chemistry, 2023)

Breakage mechanism of brown rice grain during rubber roll hulling - Peiyu Chen; Fuguo Jia; Jincheng Zhang; Yanlong Han; Anqi Li; Yinglong Wang; Jiaming Fei; Shaohang Shen; Wenyu Feng; Xianzhi Hao (Biosystems Engineering, 2023)

Numerical simulation approach for predicting rice milling performance under different convex rib helix angle based on discrete element method - Anqi Li; Fuguo Jia; Shaohang Shen; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Wenyu Feng; Jiaming Fei; Xianzhi Hao (Innovative Food Science & Emerging Technologies, 2023)

Systematical site investigation and temperature sensing in Pr3+-doped M3RE4O9 (M = Sr and Ba; RE = Sc, Y, Lu) - Xiangyu Han; Changqing Hu; Jiaming Wu; Shuxian Wang; Zhengmao Ye; Qingchun Yang (Chemical Engineering Journal, 2023)

Inspired by philosophizing of “point to area”: Ion pre-intercalation induces the reconstitution of interlayer environment of MXene for lithium storage - Miao Liu; Xin Qu; Yixuan Wang; Yukai Zhang; Cuimei Zhao; Bo Liu; Xiangxin Xue; Junkai Zhang; Zhao Wang; Jiaming Li; Wenjuan Han; Shichong Xu; et al. (Chemical Engineering Journal, 2023)

Lanthanum-modified polydopamine loaded Acinetobacter lwoffii DNS32 for phosphate and atrazine removal: Insights into co-adsorption and biodegradation mechanisms - Siyue Han; Yue Tao; Yunhe Cui; Jiaming Xu; Hanxun Ju; Linlin Fan; Lin Zhang; Ying Zhang (Bioresource Technology, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Simulations of sea fog case impacted by air–sea interaction over South China Sea - Liguo Han; Shuqin Zhang; Feng Xu; Jingjing Lü; Zebin Lu; Guiling Ye; Siqi Chen; Jianjun Xu; Jiaming Du (Frontiers in Marine Science, 2022)
A sea fog event in the South China Sea was simulated using a coupled ocean–atmosphere model (WRF for the atmosphere and ROMS for the ocean). Offshore and onshore visibility, liquid water content, air temperature, humidity, and wind speed observations and MICAPS data were utilized to validate the model results. The results of the coupled model were also compared with those of the uncoupled atmosphere model. Sea fog duration in the coupled model was closer to offshore and onshore observations, but the uncoupled model emptily forecasted offshore fog, and underreported onshore fog. Air–sea temperature difference played an important role in regulating the formation and dissipation of sea fog. The decrease of sea surface temperature in the coupled model cooled the low-level atmosphere, promoted the condensation of low-level water vapor, and increased the low-level water vapor. The decrease of air–sea temperature difference strengthened the low-level stable stratification, which weakened the horizontal wind speed and favored the formation and development of sea fog. Rising wind speed was the major driver of fog dissipation.

Study on mechanical properties and elasto-brittle-plastic constitutive model of hard brittle rock based on conventional triaxial test - Xinxin Fang; Han Tong; Jiaming Feng; Yanqiu Wang; Xiaowei Ni; Shaoyong Hou; Kang Bie (Arabian Journal of Geosciences, 2022)

Consistency correction of echo intensity data for multiple radar systems and its application in quantitative estimation of typhoon precipitation - Shuai Zhang; Jing Han; Bingke Zhao; Zhigang Chu; Jie Tang; Limin Lin; Xiaoqin Lu; Jiaming Yan (Frontiers of Earth Science, 2022)

Thrust Characteristics of Ducted Propeller and Hydrodynamics of an Underwater Vehicle in Control Motions - Jiaming Wu; Yizhe Dou; Haiyan Lv; Chenghua Ma; Le Zhong; Shunyuan Xu; Xiangxi Han (Journal of Marine Science and Engineering, 2021)
A numerical technique to simulate the hydrodynamic behavior of ducted propellers attached to an underwater vehicle traveling under the mutually interacting flow fields of the vehicle and the propellers is proposed; the hydrodynamic performance of the propellers and the hydrodynamic loading on the main body of the vehicle when it is in different kinds of motion is investigated numerically. In the research, 3D geometric models of the duct, propeller, and main body of the vehicle are first constructed according to their geometrical features. A computational fluid dynamics (CFD) technique based on the hybrid algorithm of dynamic mesh-nested sliding mesh is applied to solve the Navier–Stokes equations that govern the fluid motion around the duct, propeller, and main body of the vehicle when it is in motion. These equations are solved numerically with the CFD code Fluent. With the proposed numerical simulation technique, the hydrodynamic characteristics of the thrusts generated by the ducted propellers and the loading on the main body in the vehicle system under the mutually interacting flow fields are observed. The results of our numerical simulation indicate that the hybrid algorithm of dynamic mesh-nested sliding mesh can simulate multiple degrees of freedom of motion in underwater vehicle systems. In different motion states, the main body exerts a significant influence on the investigated flow fields; during the vehicle motions, negative wakes are formed on both sides of the main body, which lead to a decrease in the thrusts generated by the propellers on both sides. The thrust of the middle propeller is greater than that of the normal single one because of the obstructing effect in the tunnel caused by the main body.

Mapping of a major QTL for salinity tolerance at the bud burst stage in rice (Oryza sativa L) using a high-density genetic map - Lei Lei; Zhenghong Han; Bowen Cui; Luomiao Yang; Hualong Liu; Jingguo Wang; Hongwei Zhao; Wei Xin; Xianwei Li; Jiaming Li; Jingnan Cui; Shanbin Xu; et al. (Euphytica, 2021)

Maneuverability and Hydrodynamics of a Tethered Underwater Robot Based on Mixing Grid Technique - Jiaming Wu; Shunyuan Xu; Hua Liao; Chenghua Ma; Xianyuan Yang; Haotian Wang; Tian Zhang; Xiangxi Han (Journal of Marine Science and Engineering, 2021)
The maneuverability and hydrodynamic performance of the tethered underwater robot in a uniform flow field is investigated. In this research, a tethered underwater robot symmetrically installed with NACA66 hydrofoils and Ka 4-70/19A ducted propellers around its main body is first constructed. The method of overlapping grid combined with sliding mesh is applied in the numerical simulations, and the principle of relative motion is adopted to describe the hydrodynamic responses of the tethered underwater robot during the robot manipulation. The reliability of the CFD methods applied in this research is verified by experimental results, and the comparison between numerical and experimental ones shows that there is very little difference being found. The numerical results indicate that computational cost due to the research’s large-scale domain can be effectively reduced by the adopted numerical methods, hydrofoils’ control effect is greatly influenced by the towing speeds, and thrusts issued from the ducted propellers are related to the tethered underwater robot’s position and towing speed.

A wave propagation model with the Biot and the fractional viscoelastic mechanisms - Jiaming Yang; Dinghui Yang; Hongwei Han; Lingyun Qiu; Yuanfeng Cheng (Science China Earth Sciences, 2021)

Altered resting-state networks may explain the executive impairment in young health immigrants into high-altitude area - Xiaoming Chen; Jian Liu; Jiye Wang; Zhenlong Xin; Qian Zhang; Wenbin Zhang; Yibin Xi; Yuanqiang Zhu; Chen Li; Jiaming Li; Yuedong Han; Jie Liu; et al. (Brain Imaging and Behavior, 2021)

De novo assembly, transcriptome characterization, and simple sequence repeat marker development in duckweed Lemna gibba - Lili Fu; Zehong Ding; Anuwat Kumpeangkeaw; Deguan Tan; Bingying Han; Xuepiao Sun; Jiaming Zhang (Physiology and Molecular Biology of Plants, 2020)

Integrated control of tobacco black shank by combined use of riboflavin and Bacillus subtilis strain Tpb55 - Chengsheng Zhang; Jiaming Gao; Teng Han; Xueying Tian; Fenglong Wang (BioControl, 2017)

Safety Evaluation of Sevoflurane as Anesthetic Agent in Mouse Model of Myocardial Ischemic Infarction - Xiang Cheng; Jianglong Hou; Jiaming Liu; Xiaorong Sun; Qin Sheng; Pengfei Han; Y. James Kang (Cardiovascular Toxicology, 2017)

Chlorella thermophila (Trebouxiophyceae, Chlorophyta), a novel thermo-tolerant Chlorella species isolated from an occupied rooftop incubator - Shuai Ma; Bingyin Han; Volker A. R. Huss; Xiaowen Hu; Xuepiao Sun; Jiaming Zhang (Hydrobiologia, 2015)